2019
DOI: 10.1177/1077559519831382
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the Expression of Emotions by Alleged Victims of Child Abuse During Investigative Interviews Using the Revised NICHD Protocol

Abstract: Children’s testimony is often critical to the initiation of legal proceedings in abuse cases. In forensic interviews, the expression of emotions can powerfully enhance both the quality of children’s statements and perceptions that their statements are coherent and credible. However, children rarely express their emotions when reporting abusive events. The Revised The National Institute of Child Health and Human Development (NICHD) Protocol (RP) was designed to emphasize socioemotional communication during fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 69 publications
3
23
1
Order By: Relevance
“…As predicted, the present study showed that supportive nonsuggestive interviewing across the course of two interviews was associated with the enhanced willingness of suspected victims to make allegations. Previous field studies focused on the use of the RP have examined the impact of support within single forensic interviews on children’s cooperativeness (Ahern et al, 2019; Hershkowitz et al, 2015), willingness to make allegations (Hershkowitz et al, 2014; Hershkowitz & Lamb, 2020), and the quality of their forensic statements (Blasbalg et al, 2018; Blasbalg, Hershkowitz, Karni-Visel, et al, 2019; Blasbalg, Hershkowitz, Lamb, et al, 2019; Karni-Visel et al, 2019). The present results further underline the value of patiently and attentively dealing with children who are reluctant when interviewed, showing that, by providing reluctant children with support while delaying questions about the alleged abuse, interviewers may foster greater rapport and trust and increase children’s willingness to describe abusive experiences (e.g., Morrison et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As predicted, the present study showed that supportive nonsuggestive interviewing across the course of two interviews was associated with the enhanced willingness of suspected victims to make allegations. Previous field studies focused on the use of the RP have examined the impact of support within single forensic interviews on children’s cooperativeness (Ahern et al, 2019; Hershkowitz et al, 2015), willingness to make allegations (Hershkowitz et al, 2014; Hershkowitz & Lamb, 2020), and the quality of their forensic statements (Blasbalg et al, 2018; Blasbalg, Hershkowitz, Karni-Visel, et al, 2019; Blasbalg, Hershkowitz, Lamb, et al, 2019; Karni-Visel et al, 2019). The present results further underline the value of patiently and attentively dealing with children who are reluctant when interviewed, showing that, by providing reluctant children with support while delaying questions about the alleged abuse, interviewers may foster greater rapport and trust and increase children’s willingness to describe abusive experiences (e.g., Morrison et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of support during the substantive phase was positively associated with reduced reluctance and increased informativeness (Blasbalg et al, 2018). Taken together, the various components of the RP were associated with children providing richer (Blasbalg, Hershkowitz, Lamb, et al 2019) as well as more coherent (Blasbalg, Hershkowitz, Karni-Visel, et al, 2019) statements and to expressing their emotions more freely (Karni-Visel et al, 2019) than when interviewed using the SP.…”
Section: Interviewing Reluctant Childrenmentioning
confidence: 96%
“…This guidance is informed by research stressing the vital roles of rapport and trust in the abuse disclosure process (see Saywitz et al, 2015), as well as by the recognition that some children may need more time to work through suspicion or mistrust and establish rapport with interviewers (Carnes, Wilson, & Nelson-Gardell, 1999). Multiple interviews may allow trust to develop gradually as interviewer support and reassurance help dissipate negative emotions such as fear, embarrassment, or general distress associated with disclosure and/or the abuse itself (Karni-Visel et al, 2019). Thus, multiple supportive interviews may enable reluctant children to form relationships with interviewers at their own pace, making them feel more comfortable to talk about abusive experiences.…”
Section: Repeated Interviewing As a Rp Practicementioning
confidence: 99%
“…Several studies have illustrated that, following intensive training (Hershkowitz et al, 2017) in use of the RP rather than the SP, interviewers are more supportive and that this is in turn associated with reduced reluctance during the presubstantive (Hershkowitz, Lamb, Katz, & Malloy, 2015) and substantive (Blasbalg, Hershkowitz, & Karni-Visel, 2018; Blasbalg, Hershkowitz, Lamb, Karni-Visel, & Ahern, 2019) phases of individual forensic interviews, especially when the support is directly responsive to signs of reluctance (Ahern, Hershkowitz, Lamb, Blasbalg, & Winstanley, 2014; Blasbalg et al, 2018). In addition, when addressed supportively, children are also more responsive and emotionally expressive (Karni-Visel, Hershkowitz, Lamb, & Blasbalg, 2019). These reactions are associated with the provision of more information about the suspected abuse (Blasbalg, Hershkowitz, Lamb, et al, 2019; Karni-Visel et al, 2019) in the context of more coherent narratives (Blasbalg, Hershkowitz, Karni-Visel, & Lamb, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation